Design and thermodynamic analysis of a solar-assisted cini ceramic drying system - Buyukakin, Mustafa Kemalettin; Oztuna, Semiha; Demir, Hakan (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
Nowadays, solar-assisted systems have been identified as one of the best solutions to use in order to save energy in industrial processes. Energy costs and environmental pollution emanating from these proposed systems are unequivocally lower than conventional systems. In this study, a traditional Turkish cini ceramic drying kiln, with a daily capacity of 600 kg, was designed and analysed from a thermodynamic perspective. A new solar energy system was introduced, which was integrated into a drying kiln, and the size of the solar energy system components were determined. The storage capacity and the initial temperature of the water tank, the airflow rate in the drying kiln and the heat exchanger size were analysed throughout the drying process. The number of solar collectors required for the system was calculated, based on the average summer insolation conditions in Iznik, which is located in north west Turkey. A comparative analysis was undertaken to determine the daily energy savings between this solar-assisted system and conventional systems. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Solar energy; Cini ceramic drying; MASS-TRANSFER; COLLECTOR; Science & Technology - Other Topics; Energy & Fuels